The Meaning of Tomb Façades in 4th Century BC South-Western Asia Minor - Kisbali, Tamás Péter (Actual Problems of Theory and History of Art, 2017)
This article analyses the semantics of rock-cut tomb façades in 4th century Asia Minor, focusing on the ones with elements of Classical order. This type is well-attested in Lycia and Caria, especially in the borderland of these two historical regions. The monuments demonstrate a variety of architectural solutions, butthe Ionic distyle in antis can be singled out as the most popular scheme. The author’s base assumption is that these rock-cut tombs appeared under the influence of the powerful monumental architecture of the first half — middle of the 4th century BC, e.g. the Nereid Monument in Xanthos, the Heroon of Perikles in Limyra and the Mausoleum at Halikarnassos. The free-standing andron buildings are included in the list of possible prototypesas well (exemplified by the androns at the sanctuary at Labraunda). These constructions played an exceedingly important role in the life of the elites of Asia Minor. The author supposes that in the case of rock-cut tombs, it is possible to speak about not only the imitation of certain formal features, but also of the transfer of meanings.
Keywords: ancient Asia Minor; Lycia; Caria; funerary architecture; 4th century BC; late Classic period; rockcuttombs; rock-cut architecture